“Ornamenti infiniti” and Benedetto da Rovezzano’s Appeal to the Legacy of Classical Antiquity - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2015)
The article focuses on tomb monuments and decorative settings carved by a Florentine artist Benedetto da Rovezzano (1474 – after 1554), and his borrowings from Ancient Roman art. Benedetto’s narrative scenes do assume many explicit citations (motifs or isolated figures) and compositional principles from the sarcophagi reliefs. At the same time, Benedetto proves himself a direct heir of the ornamental settings of the late Quattrocento, which combine delicate form and lines with great variety of decorative motifs and animated narrative, while the problem of their arrangement is not less important than a thorough search for a direct archaeological source. The artist’s creations with their enigmatic messages composed of rich and well-elaborated decorative settings and emblems demonstrate influence of Andrea Sansovino, Giuliano da Sangallo, and strong references to Filippino Lippi, probably of a programmatic nature.